Surface attached nanobubbles and nanoparticle decorated magnetic bubbles : stability, control, and dynamics - Chan, Chon U (2015)
This thesis presents experimental studies on nanoscopic scales related to bubbles in liquids. Two objects are chosen, surface attached nanobubbles and microbubbles decorated with nanoparticles. In Part I we investigated the dynamic of surface nanobubbles. Surface attached nanobubbles are remarkably stable against diffusion and live for days. Two difficulties hinder the research on nanobubbles: First, the currently available high-resolution technique atomic force microscopy has long scan duration. Second, the sample environment is susceptible to contamination which is difficult to distinguish from the gaseous nanobubbles. To overcome these difficulties, we developed a technique to observe nanobubbles with an optical microscope. The nanobubbles adsorb a fluorescent dye and are visualized with total internal reflection fluorescent (TIRF) microscopy, which selectively excite the first 100 nm on the surface with an evanescent wave. This technique not only visualizes nanobubbles larger than 230 nm, but also resolves their subtle change in height. With this setup, we can record nanobubbles dynamic at up to 2000 frames per second to resolve fast dynamics which were previously inaccessible. Firstly we visualized the nanobubbles nucleation during water-ethanol-water exchange. The recordings show that during the mixing of ethanol and water, nanobubbles nucleate in the water-ethanol mixture and dissolve in ethanol. They are only stable in the subsequently replaced water, which agrees with the prediction of gas supersaturation after exchange. Next we detect the existence of residual flow with fluorescent tracer particles. Particle tracking results show only Brownian motion in the absence of a net flow predicted by theory. Additionally, we studied the nanobubbles coalescence dynamics. Coalescence can occur between neighboring nanobubbles or with a triple contact line. Once two neighboring nanobubbles merge under external perturbation, they grow rapidly and their contact line remains pinned. The growth dynamics can be resolved by the change in TIRF signal. The diffusion model we proposed agrees with experimental results. On the other hand, when a receding contact line meets with nanobubbles, the nanobubbles collapse. Imaging these events allows us to distinguish gaseous objects from particles and droplets. We also found that the contact line motion cannot be explained with bulk hydrodynamics but needs to account for contact line motion on a molecular level. In Part II of this thesis microbubbles coated with magnetic nanoparticles are studied. When ultrasonic driving is applied, the nanoparticles detach from the bubble's interface and are transported with the oscillatory flow field. Their trajectory can be modeled by balancing inertia and Stokes' drag. We tested the potential application in drug delivery by adding Doxorubicin capsules onto magnetic shell. We showed that the capsules can enter the cellular cytoplasm of cells located within a hydrogel. Lastly, we built a magnetic bubble trap for magnetic bubbles. There, the buoyancy is balanced with a magnetic force from a feedback-controlled electromagnet. The trap can confine the magnetic bubbles within 13μm for a long periods of time. In addition, the bubble can be translated by the magnetic field.